Potential of Telemedicine to Provide Acute Medical Care for Adults in Senior Living Communities. (13th February 2013) - Shah, Manish N.; McDermott, Ryan; Gillespie, Suzanne M.; Philbrick, Erin B.; Nelson, Dallas; Lang, Eddy
Abstract Objectives Older adults dwelling in senior living communities (SLCs) often experience barriers to medical care when they experience acute illness. The potential of telemedicine as a substitute for standard routes of evaluating and caring for individuals with acute illness (e.g., in‐person or telephone‐based interactions with primary care providers and emergency department [ED] visits) was explored in this study. Methods In this cross‐sectional, observational study, the authors conducted a 6‐month retrospective review of the medical records of adults enrolled in a university‐affiliated geriatrics practice that offers on‐site primary medical care in SLCs. For each episode of acute care, patient demographics, medical history, and chief complaint were collected and presented to an expert panel of physicians, who determined whether telemedicine could have been used to provide acute evaluation and care. The care actually provided, including outcomes, was also noted. Descriptive statistics were used to characterize the population and potential for telemedicine care. Results The medical records of 646 patients were reviewed, accounting for 1, 535 unique episodes of acute care. The expert panel identified 576 visits (38%) as potentially appropriate for telemedicine‐based acute care, with 38, 47, and 27% of phone, in‐home, and ED visits being eligible, respectively. Chief complaints most likely to be deemed potentially appropriate were falls and dermatologic, respiratory, and gastrointestinal illnesses, representing 58% of visits identified for telemedicine‐based acute care. Conclusions Telemedicine has a potentially significant role in the provision of acute care for older adults residing in SLCs. Studies are needed to evaluate the feasibility, acceptability, effectiveness, and efficiency of acute care telemedicine for this population.